2009
DOI: 10.1111/j.1872-034x.2008.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hepatic genes involved in the metabolism of fatty acids and iron in nonalcoholic fatty liver disease

Abstract: Aims: Hepatic steatosis and iron cause oxidative stress, thereby progressing steatosis to steatohepatitis. We quantified the expression of genes involved in the metabolism of fatty acids and iron in patients with nonalcoholic fatty liver disease (NAFLD). Methods:The levels of transcripts for the following genes were quantified from biopsy specimens of 74 patients with NAFLD: thioredoxin (Trx), fatty acid transport protein 5 (FATP5), sterol regulatory element-binding protein 1c (SREBP1c), fatty acid synthase (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
113
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 30 publications
15
113
0
1
Order By: Relevance
“…Although the contribution of de novo lipogenesis in the liver is very small, it has been reported that it is elevated in NAFLD, 27,28 and that the expression of ACC and FAS in the liver is increased in NAFLD patients, 29 as shown in the HFD-fed BAFF-R À / À mice in this study (Figure 4c). These data collectively indicate that the rate of fatty acid synthesis in the liver increases in HFD-fed BAFF-R À / À mice, despite the accumulation of fatty acids, and that the interaction between BAFF and BAFF-R interaction on hepatocytes may inhibit de novo lipogenesis in the liver.…”
Section: Discussionmentioning
confidence: 58%
“…Although the contribution of de novo lipogenesis in the liver is very small, it has been reported that it is elevated in NAFLD, 27,28 and that the expression of ACC and FAS in the liver is increased in NAFLD patients, 29 as shown in the HFD-fed BAFF-R À / À mice in this study (Figure 4c). These data collectively indicate that the rate of fatty acid synthesis in the liver increases in HFD-fed BAFF-R À / À mice, despite the accumulation of fatty acids, and that the interaction between BAFF and BAFF-R interaction on hepatocytes may inhibit de novo lipogenesis in the liver.…”
Section: Discussionmentioning
confidence: 58%
“…Since iron has a strong potential to produce oxidative stress, hepatic iron load is known to promote the progression of NASH (27,28). In the NAFLD liver, reduction in MTP expression levels and increased iron score were simultaneously observed during the progression of liver disease (29). Taken together, reduced MTP expression in NAFLD liver with IR or advanced steatosis may be induced by enhanced oxidative stress in these cellular circumstances.…”
Section: A a B B Cmentioning
confidence: 71%
“…However, TFR1 was markedly increased in rats with chronic hyperinsulinemia without significant alteration in TFR2, indicating that long-lasting insulin infusion upregulated TFR1 in a sustainable way through a specific mechanism that was different from that for TFR2. It has been demonstrated in clinical studies that the liver TFR1 level is significantly upregulated (Mitsuyoshi et al 2009, Tsuchiya et al 2010 in patients with DIOS and even further increased as the stage of DIOS progressed, aggravating hepatic iron overload (Mitsuyoshi et al 2009). It was also reported in clinical studies that accumulation of hepatic iron might impair the insulin effect by reducing hepatic insulin Insulin increases intracellular iron content through TFR1 in HL-7702 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Results from more recent studies demonstrated (Ruivard et al 2009, Tsuchiya et al 2010 have indicated that iron absorption was decreased in DIOS patients without altering the level of serum iron, indicating that the hepatic iron overload may be associated with cellular iron uptake, which is mainly determined by the level of TFRs. It was also reported that TFR1 level was elevated obviously in patients with DIOS (Mitsuyoshi et al 2009, Tsuchiya et al 2010) and this elevation was significantly and positively correlated with the hepatic iron content (Mitsuyoshi et al 2009). However, the effect of hyperinsulinemia on body iron stores and the level of liver TFRs remain elusive.…”
Section: Introductionmentioning
confidence: 99%